The impact of community forest concessions on income: an analysis of communities in the Maya Biosphere Reserve. (July 2018) - Bocci, Corinne; Fortmann, Lea; Sohngen, Brent; Milian, Bayron
Highlights: Concession membership has a positive effect on income relative to non-members. The income effect varies by community concession classification. Our results suggest that the income effect depends on socioeconomic characteristics. Abstract: Forests in developing tropical countries are frequently overexploited because they are essentially treated as open access due to the lack of resources dedicated to protect the area. In response, some governments have shifted towards community-based, common property resource management policies. While there is emerging evidence that these policies can reduce deforestation, there has been less research assessing the effect of these concessions on rural livelihoods. This is surprising, since sustainable income generation is an important outcome that can influence the long-term success of concession policies. This study examines the effect of community-managed forest concessions on income in the context of the Maya Biosphere Reserve in northern Guatemala. In this region, forest concessions have been established in the past 20 years to give local residents access to the forests. Residents granted access to a forest concession are required to reduce overexploitation by abiding by a sustainable forest management plan and obtaining certification from the Forest Stewardship Council. In the Maya Biosphere Reserve, the characteristics of concession communities vary and the sustainable management plan is often tailored to meet the needs of the community. The results show that the effects of participating in a forest concession on income are generally positive, although there is significant heterogeneity among communities with different socioeconomic characteristics.